An unusual synergistic adsorption of MIBC and CTAB mixtures at the air–water interface - Le, Ngoc Thu; Phan, Chi; Nguyen, A.; Ang, Ming (Elsevier, 2012)
Flotation collectors and frothers are known to synergistically adsorb at the air–water interface and reduce surface tension. Here we report an unusual synergistic adsorption of cetyl trimethyl ammonium bromide (CTAB) and methyl isobutyl carbinol (MIBC), which unexpectedly increase surface tension. The available models fail to describe the unusual increase in surface tension. A polynomial was used to empirically model the increased surface tension over entire range of mixture concentration and identify the synergistic line. The ratio of MIBC to CTAB bulk concentrations of the synergistic adsorption was greater than 100. However, the synergistic ratio of adsorbed concentrations, assuming no interaction between adsorbed molecules, varied from 2 to 5. The synergistic line can be explained by the existence of two molecular arrangements at the surface: one is dominated by MIBC and the other is dominated by CTAB. The dividing line is sharply distinguished for MIBC/CTAB systems due to the branched structure and relative position of hydrophobic group of MIBC. Mixtures of straight alcohol with CTAB show a smoother transition as previously reported in the literature. The synergism could be the underpinning principle for the superior performance of MIBC as a flotation frother.